KINERJA DAYA GENERATOR YANG DIHASILKAN DARI TURBINE CROSSFLOW DAN PELTON PADA PLTMH SKALA PROTOTYPE - M. Ikbal Sahansah; Basuki Basuki; Dian Anisa Rokhmahwati; Retno Eka Pramitasari (JURNAL ILMIAH NUSANTARA, 2024)
This research is relevant for the development of micro hydro power plants, where selecting the right turbine type can influence the output power. This research aims to compare the performance of crossflow and pelton turbines on power output for micro hydro power plants. Crossflow and pelton turbines have different characteristics in handling air flow. This research uses a quantitative approach with experimental methods. The blade shape of the crossflow turbine with blades designed to capture the air flow twice, produces a lower power of 0.70 Watts. In contrast, the Pelton turbine, with bowl-shaped blades designed to capture more air, produces higher power, namely 1.19 Watts. So the blade shape of the Pelton turbine is superior in terms of producing power.